Primary ovarian leiomyoma in young woman with premature ovarian failure - Chaudhary, Vidhi; Aggarwal, Kiran; Nangia, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Authors present a rare case of primary ovarian leiomyoma in a young female with premature ovarian failure. A 39-year-old female with premature ovarian failure presented with large unilateral adnexal mass, with mildly elevated CA-125 levels, underwent staging laparotomy where the left ovarian mass along with tubes was removed. Contralateral ovary and uterus were preserved. Final diagnosis was Primary ovarian leiomyoma on histopathology and immunohistochemical analysis. Preoperative diagnosis is difficult with solid ovarian tumors. In presence of mildly elevated CA-125 and negative tumor markers, ovarian leiomyoma must be considered as a differential diagnosis and conservative surgery be planned as these patients are desirous of future fertility options. Definitive diagnosis is confirmed by histopathology and immunohistochemical analysis.